Resolution of Agrarian Conflict in the Santoso Area of Palembang City (A Case Study of Authorities and Community in the Santoso, Palembang City) - Adhyasa, Wahyu Pratama (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2023)
The title of this study is